2-chloromuconate and ClcR-mediated activation of the clcABD operon: in vitro transcriptional and DNase I footprint analyses. - McFall, S M (1997)
In Pseudomonas putida, the plasmid-borne clcABD operon encodes enzymes involved in 3-chlorocatechol degradation. Previous studies have demonstrated that these enzymes are induced when P. putida is grown in the presence of 3-chlorobenzoate, which is converted to 3-chlorocatechol, and that ClcR, a LysR-type regulator, is required for this induction. The clcABD operon is believed to have evolved from the chromosomal catBCA operon, which encodes enzymes that utilize catechol and is regulated by CatR. The inducer for the catBCA operon is an intermediate of the catechol pathway, cis,cis-muconate. In this study, we demonstrate by the use of in vitro transcription assays and lacZ transcription fusions in vivo that the analogous intermediate of the 3-chlorocatechol pathway, 2-chloromuconate, is the inducer of the clcABD operon. The DNase I footprints of ClcR with and without 2-chloromuconate were also determined. An extended region of the promoter from -79 to -25 was occupied in the absence of inducer, but the -35 region was unprotected. When 2-chloromuconate was added to the binding assays, the footprint contracted approximately 4 bp at the proximal end of the promoter, and the -35 region was contacted. It is interesting to note that CatR actually extends its footprint 14 bp on the catBCA promoter in response to its inducer. Although CatR and ClcR change their nucleotide protection patterns in different manners when exposed to their respective inducers, their final footprints resemble each other. Therefore, it is possible that their transcriptional activation mechanisms may be evolutionarily conserved.